2022
DOI: 10.1007/s11046-022-00627-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Mortality of COVID-19-Associated Mucormycosis: A Systematic Review and Meta-Analysis

Abstract: The recent increase of COVID-19-associated mucormycosis (CAM) has been commanding global attention. However, basic epidemiologic characteristics have not firmly been established. In this systematic review and meta-analysis, we sought to determine the clinical manifestations, potential risk factors, and outcomes of CAM. Observational studies reporting CAM were searched with PubMed and EMBASE databases in January 2022. We collected data on comorbidities and treatment for COVID-19, and performed a one-group meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 83 publications
(126 reference statements)
3
22
1
5
Order By: Relevance
“…Besides dysfunction of the olfactory nerve, other cranial nerves are occasionally affected following SARS-CoV-2 infection and secondary to long-term treatment with steroids in patients who are usually immunocompromised. Such patients might catch rhino-orbito-cerebral mucormycosis with infiltration of the orbital cavity, or nasal sinuses with affection of oculomotor, abducent, trochlear and optic nerves with or without cavernous sinus thrombosis [42,43].…”
Section: Neuropsychiatric Aspects Of Sars-cov-2 and Mpxmentioning
confidence: 99%
“…Besides dysfunction of the olfactory nerve, other cranial nerves are occasionally affected following SARS-CoV-2 infection and secondary to long-term treatment with steroids in patients who are usually immunocompromised. Such patients might catch rhino-orbito-cerebral mucormycosis with infiltration of the orbital cavity, or nasal sinuses with affection of oculomotor, abducent, trochlear and optic nerves with or without cavernous sinus thrombosis [42,43].…”
Section: Neuropsychiatric Aspects Of Sars-cov-2 and Mpxmentioning
confidence: 99%
“…The clinical form depends on the risk factor and predisposing condition; ROCM is frequently observed in association with uncontrolled DM and DKA, whereas pulmonary involvement is often observed in patients having neutropenia, HSCT, SOT, and hematological malignancies, while gastrointestinal tract (GIT) gets involved more in malnourished individuals and cutaneous form following trauma [ 1 , 10 , 11 ••, 22 ]. The most common type of CAM was ROM or ROCM followed by pulmonary and others (cutaneous, renal, gastrointestinal, disseminated) [ 19 ••, 24 ••, 33 ].…”
Section: Pathogen Factorsmentioning
confidence: 99%
“…In a systematic review and meta-analysis, Watanabe et al reported DM as the underlying disease in 82% and administration of corticosteroids in 77% patients of CAM [ 33 ]. In a multi-center epidemiologic study from India, Patel et al reported DM in 60.4% and administration of corticosteroids in 78.7% patients with CAM [ 19 ••].…”
Section: Pathogen Factorsmentioning
confidence: 99%
See 2 more Smart Citations